Furthering taekwondo as an academic discipline: A report on Youngsan University’s 1st International Academic Taekwondo Conference (Revista de Artes Marciales Asiáticas, 2019)
The 1st International Academic Taekwondo Conference Youngsan University was held on October 4, 2019 in Yangsan, Republic of Korea (ROK; i.e., South Korea). In an effort to bring together international researchers of taekwondo, three non-Korean presenters were invited and three accomplished academics, two non-Korean, made up the conference’s invited panelists. The topics presented were: 1) the shift in taekwondo’s peace promotion duties, 2) a discussion of mudo (“martial way” of life) in the Democratic People’s Republic of Korea (DPRK; i.e., North Korea), and 3) the decline of taekwondo as a combat sport. Although small in scale, the conference built upon previous taekwondo academic endeavors in- and outside of Korea. Most importantly, the conference highlighted the fact that non-Korean academics are furthering the research field beyond the nationalistic concepts still held in the Korean taekwondo community. The event immediately garnered interest in an expanded conference for 2020.